Polyoxidonium® Activates Cytotoxic Lymphocyte Responses Through Dendritic Cell Maturation: Clinical Effects in Breast Cancer - Alexia, Catherine; Cren, Mailys; Louis-Plence, Pascale; Vo, Dang-Nghiem; El Ahmadi, Yasamine; Dufourcq-Lopez, Emilie; Lu, Zhao-Yang; Hernandez, Javier; Shamilov, Farkhad; Chernysheva, Olga; Vasilieva, M.; Vorotnikov, I.; et al. (Frontiers in Immunology, 2019)
Immunotherapy, which is seen as mayor tool for cancer treatment, requires in some cases the presence of several agents to maximize its effects. Adjuvants can enhance the effect of other agents. But despite their long-time use, only a few adjuvants are licensed today and their use in cancer treatment is scarce. Azoximer bromide, marketed under the trade name Polyoxidonium® (PO), is the copolymer of N-oxide of 1,4-ethylenepiperazine and (N-carboxyethyl)-1,4-ethylene piperazinium bromide. It was described as an immune adjuvant and immunomodulator used that is clinically used with excellent tolerance. PO is used in treatment and prophylaxis of diseases connected with damage of immune system and there is an interest to test it in antitumor therapy. We show here that PO treatment for one week induces positive pathological changes in 6 out of 20 patients with breast cancer, including complete response in a triple negative patient. This correlated with increased percentage of tumor CD4+ T-lymphocytes infiltrating rate. PO immune effects are associated with myeloid cell activation and little is known about PO action on the lymphocyte lineages such as natural killer (NK) and T cells. We reveal that PO increases T cell proliferation in vitro without negative effects on any activation marker. PO does not affect dendritic cell (DC) viability and increases expansion of immature DC (iDC) and mature DC (mDC) at 100 µg/ml and stimulates expression of several DC co-stimulatory molecules inducing proliferation of allogeneic T cells. In contrast, PO decreases DC viability when added at day 5 post-expansion. PO is not toxic for NK cells at doses up to 100 µM and does not affect their activation, maturation and cytotoxicity, but tends to increase degranulation. This could be beneficial against target cells that show low sensitivity to NK cells, e.g. solid tumor cells. Finally, we have found great variability of PO responses between donors. In summary, our in vitro results show that PO increases the number of costimulatory molecules on DC that prime T cells favoring the production of effector T cells. This may support future clinical development of PO in cancer treatment.